Объяснение:
(Х-у=3
(Х+у=5
Х=3+У
3+у+у=5
2у=5-3
У=2÷2
У=1
Х-1=3
Х=3+1
Х=4
(4-1=3
(4+1=5
(4;1)-ответ
сложения
Х-у=3
Х+у=5
(Х-у)+(х+у)=3+5,скобки раскрываем получаем
Х-у+х+у=8,-у сокращаем,получаем
2х=8
Подставляем в любое уравнение
4-у=3
У=4-3
Объяснение:
(Х-у=3
(Х+у=5
Х=3+У
3+у+у=5
2у=5-3
У=2÷2
У=1
Х-1=3
Х=3+1
Х=4
(4-1=3
(4+1=5
(4;1)-ответ
сложения
Х-у=3
Х+у=5
(Х-у)+(х+у)=3+5,скобки раскрываем получаем
Х-у+х+у=8,-у сокращаем,получаем
2х=8
Х=4
Подставляем в любое уравнение
4-у=3
У=4-3
У=1
(4-1=3
(4+1=5
(4;1)-ответ